Niveles de abono orgánico en la captura de carbono y eficiencia fotosintética del Zea mays (maíz) en Loreto 2024 - Sanchez Shapiama, Jose Mercedes (2024)
The experimental test was developed in the Agrostology Project, in the Zungarococha farm, the purpose was to evaluate the effect of doses of organic fertilizer (chicken manure) plus a bottom fertilizer (ash) on carbon capture and photosynthetic yield in corn cultivation, evaluated at (60 days), the work was experimental with a population of 480 plants and taking as a sample 4 plants / treatment, the ash was incorporated 3 days (3 kg / m2) before applying the organic fertilizer according to the treatments, tabulating the data and according to the results it is concluded: That there are effects in the treatments and in the variables studied in corn, where T3 (4 kg of chicken manure / m2 + 3 kg / m2 of ash) occupied the first order with averages of: (Green matter = 4.60 kg / m2; Dry matter = 0.96 kg / m2, Photosynthetic E. = 0.22% and Carbon Capture = 0.368 kg/m2). Therefore, the hypothesis proposed is rejected and the alternative accepted, since in the evaluations after 60 days there is an influence of the fertilizers applied to the corn crop.